2011
DOI: 10.1111/j.1469-0691.2010.03357.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparison of galactomannan in bronchoalveolar lavage fluid for the diagnosis of pulmonary invasive aspergillosis in medical patients under intensive care: comparison with the diagnostic performance of galactomannan and of (1→ 3) – β – d-glucan chromogenic assay in serum samples

Abstract: Diagnosis of fungal pneumonia (FP) in critically ill patients is challenging. Circulating biomarkers for the diagnosis of FP have limitations and the combination of different assays in serum samples and directly from the target organ may further improve the diagnosis of FP. We prospectively assessed the diagnostic utility of paired galactomannan (GM) in bronchoalveolar lavage fluid (BAL) and serum GM and (1→3)-β-D-glucan (BG) assays in critically ill patients at risk of FP. Patients with FP were classified acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 28 publications
1
73
1
5
Order By: Relevance
“…This finding is clinically relevant not only for the population to which the prediction rule can be applied, but also because it is very easy to remember and may help intensivists to decide when to start antifungal treatment. A few studies have investigated the predictive value of BDG on IC in non-neutropenic critically ill patients [21][22][23][24][25]. Elevated concentrations of BDG have been reported to be associated with other fungi, such as Pneumocystis jirovecii infections [26], Gram-positive and Gram-negative bloodstream infections, exposure to gauze or other materials that contain glucans, biofilms on vascular catheters, hemodialysis, and administration of a,b Superscripts indicate significant differences (P \ 0.05) among rates of BDG and positive CAGTA values among the three study groups Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is clinically relevant not only for the population to which the prediction rule can be applied, but also because it is very easy to remember and may help intensivists to decide when to start antifungal treatment. A few studies have investigated the predictive value of BDG on IC in non-neutropenic critically ill patients [21][22][23][24][25]. Elevated concentrations of BDG have been reported to be associated with other fungi, such as Pneumocystis jirovecii infections [26], Gram-positive and Gram-negative bloodstream infections, exposure to gauze or other materials that contain glucans, biofilms on vascular catheters, hemodialysis, and administration of a,b Superscripts indicate significant differences (P \ 0.05) among rates of BDG and positive CAGTA values among the three study groups Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for ICU admission was medical in 18.8 % of patients, surgical in 76.1 %, and trauma in 5.1 %. The median (IQR) length of ICU and hospital stay was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) and 38 (24-57) days, respectively, which were significantly higher in patients with IC compared to the other two groups. ICU and hospital crude mortality rates were 26.7 and 32.4 %, respectively.…”
Section: Study Population and Salient Findingsmentioning
confidence: 95%
“…This results show that the detection of GM in BAL fluid enhances the identification of Aspergillus species as a cause of pulmonary disease in ICU patients. The result of several studies have also shown that the GM analysis of BAL samples should consider for IA diagnosis among high-risk patients, especially for the ease of processing and the more rapid result than traditional methods (1,23,29). Moreover, all patients with probable IA had at least one positive BAL GM index, in the present study.…”
Section: Discussionmentioning
confidence: 48%
“…Así, se ha reportado su positivización precoz antes del inicio de los síntomas o de los signos radiológicos de EFI [9][10][11][12] . Este test también se ha evaluado en pacientes cursando una infección por Pneumocystis jiroveci donde se observan concentraciones elevadas de BDG, con alta sensibilidad y buen valor predictor positivo 17,18 . Existen pocos datos sobre el rendimiento de la medición del BDG en pacientes críticos.…”
Section: Introductionunclassified